Effect of Magnetic Water Treatment on Prevention of CaCO3 Scales (Baghdad Science Journal, 2013)
Permanent magnets of different intensities were used to investigate the effect of a magnetic field in the process of preventing deposits of calcium carbonate. The magnets were fixed on the water line from the tap outside. Then heating a sample of this water in flasks and measuring the amount of sediment in a manner weighted differences. These experiments comprise to the change of the velocity of water flow, which amounted to (0.5, 0.75, 1) m/sec through the magnetic fields that are of magnetic strength (2200, 6000, 9250, 11000) Gauss, and conduct measurements, tests and compare them with those obtained from the use of ordinary water.The results showed the effectiveness of magnetic treatment in reducing the rate of deposition of calcium carbonate where up to 60% after treatment, and this percentage is increasing with increasing magnetic field strength where up to 85% when the intensity of the magnetic field 9250 and 11000 Gauss at the velocity of the water flow of 0.75 m/sec. This percentage of reducing was investigated with increasing the velocity of flow of water through a magnetic field. Also the results showed an increase in total dissolved solids (TDS) as well as electrical conductivity and a decrease in the value of surface tension as a result of magnetic treatment.Observation with the photograph pictures of the distillation apparatus oriented in several laboratories, that the amount of sediment formed a thick layer in the device-free magnetic treatment, but it was not dense and in the few quantity in the apparatus treated with magnetic intensity (8000, 9250) Gauss.